Skrivnostno spletno življenje mladostnikov ter internetne nevarnosti - Rizman Herga, Nataša (Revija za elementarno izobraževanje, 2012)
For young people, the Internet is a medium and the technology of their childhood and their adolescence. One of the main motives for spending leisure time behind a computer is the inclination towards social interactions in virtual environments. Moreover, the virtual space gives adolescents an opportunity to satisfy their needs for self-expression, self-assessment, research, and experimentation with their identity. It gives them the feeling of freedom, fun, relaxation, and comfort. Yet leisure time spent on social networking or in the virtual world poses a risk for the youth. With this in mind, we have carried out a survey among pupils of the 8th and 9th grades of elementary school (N = 80). We focused on the awareness regarding the use of the Internet, with a hint of the social networks phenomenon based on Facebook. The results have shown that parents were generally not aware of the online lives of their teens, which means that adolescents can easily get caught in the traps of the Internet.
Keywords: internet; mladostniki; adolescent; safe use; varna uporaba